HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU TERHADAP INFEKSI MENULAR SEKSUAL PADA REMAJA DI COMORO DILI TIMOR-LESTE - Januario Nuno Dos Reis Gomes; Ni Luh Putu Suariyani (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2023)
Sexually Transmitted Infections (STIs) are global public health problems. Adolescents are a vulnerable age group of STIs. This study aims to determine the relationship between knowledge and attitudes and behaviors towards STIs in adolescents in Comoro, Dili, Timor-Leste. This study was descriptive with a cross-sectional approach conducted in Canossa highschool and Externato de São Jose highschool from April-June 2022. The independent variables were knowledge and attitude, the dependent variable was adolescent behavior. The sample of this study was adolescents in 15-18 years old in Canossa highschool and Externato de São Jose and willing to become the respondent, 85 adolescents were selected as respondent. The results showed that 71.8% of respondents have good knowledge, 67.1% of respondents have good attitudes and 75.3% of respondents have good behavior in relation to STIs. The results of the analysis of the relationship between knowledge and attitudes to risk behavior for STIs 83.6% of respondents were categorized as good knowledge and have good behavior in relation to STIs and 84.2% of respondents were having good attitudes and have good behavior in relation to STIs. The results of the chi-square statistical test on knowledge and attitude variables obtained a p-value of 0.01, therefore, there is a significant relationship between the knowledge and attitudes of respondents regarding risk behavior for STIs. Comprehensive education regarding sexual health is needed for adolescents in Comoro Dili Timor-Leste. Keywords: Adolescents, STIs, HIV, Infectious diseases.